Urgensi Revisi Undang-Undang Nomor 6 Tahun 2014 Tentang Desa Perihal Pembangunan Desa - Herdiana, Dian (Jurnal Hukum & Pembangunan, 2020)
The enactment of Law Number 6 of 2014 on Villages brings optimism to the creation of village development that is able to realize village autonomy. But in practice, the Village Law has not been able to realize the development goals. On this basis, this article is intended to examine village development from the perspective of the substance of the Village Law. The method used in this study is a juridical-normative method with a descriptive approach. The results of the study show that the substance of the Village Law does not give full authority to the villages in local-participatory development, even the Village Law still provides opportunities for local governments to intervene in the implementation of development. The mechanism stipulated in the Village Law makes the village busy with administrative obligations in village development. The implication is that although the village is no longer a vertical government structure under the Regency/City government, empirically the role of the Regency/City government is still dominant. These problems construct a substantial impulse to revise the Village Law, specifically regarding arrangements for village development.